AN EVALUATION OF UNILATERAL SPINAL ANAESTHESIA FOR INGUINAL HERNIA REPAIR: A PROSPECTIVE RANDOMISED COMPARATIVE STUDY. - Tarannum, Nazia; Hoda, Ilmul (Student’s Journal of Health Research Africa, 2024)
Introduction Around the world, repair of inguinal hernia is frequently utilized in the Lichtenstein mesh repair process. While hernioplasty performed under local anesthesia undoubtedly offers significant advantages, it has yet to be established as a routine practice. The purpose of this study is to provide additional information about this situation and the findings of a comparison between Lichtenstein hernioplasties carried out under local anesthesia and spinal anesthesia. Methods By calculating the sample size, 60 patients were chosen for this non-randomized clinical investigation. Thirty patients underwent local anesthesia during their operations, while thirty more underwent spinal anesthesia. Results Compared to spinal anesthesia, the average operating time under local anesthesia was slightly greater, at 62.5 minutes (SD=17.8) instead of 51.1 minutes (SD=21.5). At six, twelve, and twenty-four hours after surgery, the pain was significantly less in the local anesthetic group than in the spinal anesthesia group (p=0.04, p=0.042, and p=0.041, respectively). Following spinal anesthesia, headaches, urinary retention, and hypotension were more common postoperative sequelae than those following local anesthetic. The local anesthesia group’s hospital stay lasted 24.5 hours (SD=12.8), a considerable reduction from the spinal group’s 57.1 hours (SD=16.7). Conclusion Compared to spinal anesthesia, postoperative problems such as headache, hypotension, and urine retention were less noticeable in the group under local anesthesia. There was also a substantial decrease in postoperative pain. Therefore, the study finds that the use of local anesthetics for Lichtenstein hernioplasty procedures in place of spinal anesthesia is the standard method of anesthesia. Recommendation Avoiding physically demanding tasks that can cause a hernia is advised.